THE ANALYSIS OF REPETITION AS PART OF LEXICAL COHESION IN TALK SHOWS - zia hisni mubarak (BASIS (Bahasa dan Sastra Inggris), 2019)
The aim of this paper is to define the lexical cohesion in the dialogue. The focus of this paper is the repetition that happens frequently in the dialogue. The dialogue is taken from the talk shows downloaded from youtube. The analysis is given based on the data from the dialogue of the speakers and draw the conclusion. This study brings benefits in building the perception of the audiences. From the data that has been analyzed, it has been found that the speakers tend to repeat the word, phrase, or sentence because they want to strengthen their opinion, eventhough from the sentence structure the repetition is not good and eficient. The result of the study also show that there are some reasons why do the speakers repeat their word. phrase or sentence such as to strengthen their opinion.